Healthy minds: Psychosocial interventions for school-aged children affected by HIV/AIDS - Cluver, L.; Kganaka, M.; Boyes, Mark; Park, M. (Oxford University Press, 2012)
This chapter focuses on interventions that foster social integration, reduce psychosocial problems, and promote resilience among school-aged children affected by HIV/AIDS. The chapter discusses the psychosocial needs specific to this population group, describes the mechanisms by which familial HIV/AIDS may affect the psychosocial development of children, and analyzes the effectiveness of a range of existing psychosocial interventions.